Project-Based-Learning and Flipped Classroom Method on Students’ Reading Comprehension - Mumtazah, Livia Dwi; Rukminingsih, Rukminingsih; Ifnaruddin, Didik (Universitas Pendidikan Ganesha, 2024)
Learning has been required to be innovative and digital-based with student-centered learning which ultimately with the Pancasila student profile they are able to express their ideas and thoughts in a project that will be exhibited to exchange information with other students. This study aims to analyze the effectiveness of the combination of project-based learning (PjBL) and flipped class (FC) methods on students' reading comprehension in high school. This study is a quantitative quasi-experimental study with nonequivalent to conduct an analysis consisting of an experimental class and a control class. The researcher used a data collection method by taking tests and conducting pre-test and post-test trials. Students' tryout scores were calculated using statistical formulas. This study reveals aspects of reading comprehension, determining the main idea (1), finding references (2), making conclusions (3), detailed information (4), and understanding vocabulary (5). This study involved 68 students from two classes and used a quasi-experimental design with a post-test only control design. Data were collected using a background knowledge test and a post-test. The results showed that the experimental class had a higher average score (81.03) than the control class (63.53). This study revealed that the combination of PjBL and FC methods is effective to be used as a learning media. The implication of this study is Integrating PjBL and FC in EFL reading teaching where the results obtained are able to improve active learning, positive student attitudes, and effective use of online learning resources, as well as encourage student participation and grades.